2021
DOI: 10.1093/rb/rbab057
|View full text |Cite
|
Sign up to set email alerts
|

A bifunctional MXene-modified scaffold for photothermal therapy and maxillofacial tissue regeneration

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common malignant tumours in the oral and maxillofacial regions and is highly malignant and prone to recur despite the development of various effective treatments, including surgery and chemoradiotherapy. Actually, it is difficult to ensure the complete elimination of tumour cells, and maxillofacial bone defects caused by surgery are hard to heal by themselves. In addition, chemoradiotherapy can bring serious side effects. Therefore, it is imperative to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In previous studies, New Zealand white rabbits were used to establish infected condyle defect model by creating a cylinder-shaped bony defect (6 mm × 4 mm) perpendicular to the femoral shaft to verify the HACC-grafted PLGA/HA scaffolds with significantly enhanced anti-infection and bone regeneration efficacy [ 30 ]. Li et al reported a bifunctional M-CSH scaffold by building a round critical bone defect with a diameter of 6 mm at the mandibular body [ 28 ]. In this study, in order to adapt the bone defect model to the square 3D printed scaffold, we modified the construction method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, New Zealand white rabbits were used to establish infected condyle defect model by creating a cylinder-shaped bony defect (6 mm × 4 mm) perpendicular to the femoral shaft to verify the HACC-grafted PLGA/HA scaffolds with significantly enhanced anti-infection and bone regeneration efficacy [ 30 ]. Li et al reported a bifunctional M-CSH scaffold by building a round critical bone defect with a diameter of 6 mm at the mandibular body [ 28 ]. In this study, in order to adapt the bone defect model to the square 3D printed scaffold, we modified the construction method.…”
Section: Discussionmentioning
confidence: 99%
“…The MC3T3-E1 cell was selected to study the cytotoxicity and biological compatibability of the scaffold [ 28 ]. The KSL-W@PLGA/COL/SF/nHA scaffold was gently placed on 24-well plates, and the MC3T3-E1 cell was seeded onto it at a density of 2 × 10 4 /mL and cultured for 3 days, 5 days, 7 days and 10 days respectively, and then 50 μL cck-8 solution was added to each well of the 24-well plate and incubated for 4 h, and measured spectrophotometrically at 450 nm wavelength.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[194] Ti 3 C 2 T x -CSH scaffold Maxillofacial tissue regeneration MXene-CSH scaffold stimulated the in vivo formation of maxillofacial bone, and induced the osteogenic protein expression of MC3T3-E1 in vitro. [195] Nb 2 C@Titanium plate Tissue regeneration…”
Section: Tissue Engineeringmentioning
confidence: 99%